2021
DOI: 10.1186/s12864-021-08001-6
|View full text |Cite
|
Sign up to set email alerts
|

Revelation of candidate genes and molecular mechanism of reproductive seasonality in female rohu (Labeo rohita Ham.) by RNA sequencing

Abstract: Background Carp fish, rohu (Labeo rohita Ham.) is important freshwater aquaculture species of South-East Asia having seasonal reproductive rhythm. There is no holistic study at transcriptome level revealing key candidate genes involved in such circannual rhythm regulated by biological clock genes (BCGs). Seasonality manifestation has two contrasting phases of reproduction, i.e., post-spawning resting and initiation of gonadal activity appropriate for revealing the associated candidate genes. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 134 publications
1
1
0
Order By: Relevance
“…As we had to identify genes linked to high body weight concurrent with high EBV, we selected six fish/groups, i.e., LB and HB, based on earlier reports ( Danzmann et al, 2016 ; Lin et al, 2019 ; Shen et al, 2022 ). Clean and trimmed reads generated had GC content ranging from 37% to 42%, which is similar to previous reports ( Das et al, 2020 ; Jaiswal et al, 2021 ). BUSCO analysis indicated that our transcriptome had partial to complete gene information for 86.31% of the genes when compared with the eukaryote orthologous set.…”
Section: Discussionsupporting
confidence: 89%
“…As we had to identify genes linked to high body weight concurrent with high EBV, we selected six fish/groups, i.e., LB and HB, based on earlier reports ( Danzmann et al, 2016 ; Lin et al, 2019 ; Shen et al, 2022 ). Clean and trimmed reads generated had GC content ranging from 37% to 42%, which is similar to previous reports ( Das et al, 2020 ; Jaiswal et al, 2021 ). BUSCO analysis indicated that our transcriptome had partial to complete gene information for 86.31% of the genes when compared with the eukaryote orthologous set.…”
Section: Discussionsupporting
confidence: 89%
“…It has been found that animal reproduction activity varies with the seasons, which is not only related to the ambient temperature and light, but also closely related to the endogenous regulation of animals themselves. Studies have shown that genes involved in the regulation of animal reproduction change rhythmically with the seasons and play an important role in the regulation of seasonal reproduction ( 1 ). The reproductive activity of seasonal breeding animals is governed by a regulatory network of the Pineal—Hypothalamus—Pituitary—Ovary (PHPO) axis.…”
Section: Introductionmentioning
confidence: 99%